The Interaction Effect of Birth Spacing and Maternal Healthcare Services on Child Mortality in Pakistan - Muhammad Farhan Asif; Saima Ishtiaq; Nishat Ishfaq Abbasi; Iffat Tahir; Ghulam Abid; Zohra S. Lassi (MDPI AG, 2023)
There is widespread agreement that improved health should be regarded as a means and an end in the context of the development process. The health of the populace and the equitable provision of healthcare are two indicators of a society's level of development. A variety of factors influences child mortality. This study investigated the causes of child death and the interaction effect of birth spacing (B.S.) and maternal health care services (MHCS) on child mortality. Using SPSS version 20, we used the Pakistan Demographic and Health Survey (PDHS) 2017-2018 data set to investigate the associated factors of child mortality and the moderating influence of birth spacing using binary logistic regression. The outcome variable is categorical with two categories. The findings indicated that the risk of infant death decreased with adequate B.S. between two pregnancies and access to maternal health care services. Birth spacing was found to moderate the link between access to maternal health care services (MHCS) and child mortality. Our research leads us to conclude that the amount of time between children's births significantly reduces infant mortality. When the birth spacing is at least 33 months, the relationship between maternal health care services and child mortality becomes more evident and negative.